Characterization of chemical compound and cellulose content in kenaf core: article - Zakaria, Siti Raihan; Abdol Aziz, Rabiatul Adawiyah (2017)
In this study, the chemical composition and cellulose content of kenaf core were investigated. Kenaf core was pretreated with 4 wt% sodium hydroxide (NaOH) followed by five steps of bleaching using 1.7 wt% sodium chloride (Nacl) in acetic acid buffer solution. The effects of five steps bleaching on the cellulose content was also investigated. Raw kenaf core, alkaline-treated kenaf core, 1st bleaching kenaf core, 3rd bleached kenaf core and 5th bleached kenaf core were analyzed by using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA) and X-ray diffractometer (XRD). The effectiveness of alkaline treatments in the removal of non-cellulosic materials which is lignin and hemicellulose from the kenaf core fiber was confirmed by Fourier Transform Infrared Spectroscopy (FTIR) observation. The crystallinity of all the samples were calculated by using Segal method. X-ray diffractometer analysis showed that the 5th bleached kenaf core has the highest degree of crystallinity which is 76.4 % while raw kenaf core show the lowest which is 55.8%. The increasing of crystallinity for each subsequent sample improved that the removal lignin and hemicellulose after the treatment. Thermal analysis results show that the content of cellulose is increased after subsequent chemical treatment.